Book Review: Reading the Term Dalâl in The Qur’an - A.Baliyo Eko Prasetyo (Millah: Journal of Religious Studies, 2008)
Book          : Kesesatan dalam Perspektif Al-Qur’anAuthor        : Aibdi RahmatPublisher    : Pustaka Pelajar, YogyakartaEdition        : I, March 2007Content      : viii + 228 pages